«Melancholy of spring». The loss of nature in the early works of Attilio Bertolucci (ENTHYMEMA, 2022)
The impressionistic representations of the landscape that characterise Attilio Bertolucci’s first verse production speak in the background of a loss of nature on the part of the poetic subject. Starting from some of the author’s juvenile prose and then examining Sirio and Fuochi in novembre, the article aims, first of all, to delineate such an experience. This allows, afterwards, to reconsider the enunciative posture typical of Bertolucci’s poetry, that of the lyric self describing the rural landscape, and above all the role of the gaze, which, as a result of the analysis carried out, shows its character of limit alongside that of fundamental cognitive resource. Finally, the article identifies the reasons for the loss, which can be traced back to the corrosive action of time and the imprisonment caused by life in the city, and the profound symbolic meaning of the separation from nature.
Keywords: Nature; Time; City; Gaze; Identity